Challenges and Approaches of the Global Governance of Public Health Under COVID-19 - Zhang, Hu (Frontiers in Public Health, 2021)
Public health events, as the common concern faced by the international community, call for the joint response from all mankind. The outbreak of the COVID-19 has highlighted the problems confronting the global governance of international public health, such as limited functions of international organizations and difficulties in achieving objectives, poor collaboration between governance subjects and their limited performance, overlapping legal basis of governance and blurred core function, and lack of solutions to special problems. The corresponding approaches can be taken to improve the efficiency of the governance of global public health, including supporting the role of international organizations to achieve the objectives, enhancing coordination among international governance subjects to form synergy, promoting the compliance with IHR2005 to avoid conflict of law application and upholding the vision of a community with a shared future for mankind to jointly respond to the special problems.